Phytohormones regulate the abiotic stress: An overview of physiological, biochemical, and molecular responses in horticultural crops - Zheng, Yi; Wang, Xiaonan; Cui, Xin; Wang, Kefeng; Wang, Yong; He, Yuhui (Frontiers in Plant Science, 2023)
Recent changing patterns of global climate have turned out to be a severe hazard to the horticulture crops production. A wide range of biotic and abiotic stresses often affect plants due to their sessile nature. Horticultural crop losses are mainly caused by abiotic factors such as drought, salt, heat, cold, floods, and ultraviolet radiation. For coping up with these adversities, well-developed mechanisms have been evolved in plants, which play a role in perceiving stress signals and enabling optimal growth responses. Interestingly, the use of phytohormones for suppressing the impact of abiotic stress has gained much attention in recent decades. For circumvention of stress at various levels, including physiological, molecular, as well as biochemical, a sophisticated mechanism is reported to be provided by the phytohormones, thus labelling these phytohormones a significant role in plant growth and development. Phytohormones can improves tolerance against abiotic stresses by increasing seed germination, seedling growth, leaf photosynthesis, root growth, and antioxidant enzymes and reducing the accumulation of reactive oxygen species, malonaldehyde, and electrolyte leakage. Recent discoveries highlight the significant role of a variety of phytohormones including melatonin (MEL), Gamma-aminobutyric acid (GABA), jasmonic acid (JA), salicylic acid (SA), brassinosteroids (BRs), and strigolactones (SL) in abiotic stress tolerance enhancement of horticultural plants. Thus, current review is aimed to summarize the developmental concepts regarding role of phytohormones in abiotic-stress mitigation, mainly in horticultural crops, along with the description of recent studies which identified the role of different phytohormones in stressed environments. Hence, such a review will help in paving the path for sustainable agriculture growth via involvement of phytohormones in enhancement of abiotic stress tolerance of horticultural crops.